Prevalence of goitre and associated factors among school-aged children in Guraferda District, Southwest Ethiopia - Tuke, Gemechis; Mengistu, Walelign; Kuratu, Kidist; Elias, Sebsibe; Gelchu, Miesa (Frontiers in Public Health, 2025)
IntroductionGoitre is a significant public health problem, particularly in underdeveloped countries like Ethiopia. Iodine Deficiency Disease is the leading cause of preventable brain injury in children, resulting in poor academic performance.ObjectivesTo determine the prevalence of goitre and associated factors among children aged 6–12 years in Guraferda District, Southwest Ethiopia in 2024.MethodsA community cross-sectional survey was conducted with 949 children ages 6–12 years who lived in selected kebeles in Guraferda District. Structured questionnaires, physical examinations, and iodized salt tests were all used to collect data. To identify factors related with goitre, a logistic regression analysis was performed using SPSS version 26. Statistical significance was determined at p < 0.05 using adjusted odds ratios and 95% confidence intervals.ResultsThe prevalence of Goitre among school-age children in this study was 37.6, 95% CI: 34.4, 40.8%. Female gender (AOR = 1.614, 95% CI: 1.199, 2.172), mothers with non-formal education (AOR = 1.93, 95% CI: 1.437, 2.592) (AOR = 1.93, 95% CI: 1.44, 2.592), rural residence (AOR = 2.291, 95% CI: 1.162, 3.239), storing salt near heat sources (AOR = 1.407, 95% CI: 1.042, 1.900), low food diversification status (AOR = 4.928, 95% CI: 3.332, 7.289), and consuming cabbage at least once a week (AOR = 2.874, 95% CI: 2.012, 4.106) were positively associated with Goitre, while consuming milk at least once a week (AOR = 0.217, CI: 0.145, 0.324) was negatively associated with Goitre.ConclusionThe study findings indicate a high prevalence of Goitre in the area. Factors such as being female, living in rural areas, mothers with no formal education, storing salt near heat sources, consuming cabbage, and low food diversification were associated with increased odds of Goitre. Therefore, it is recommended to ensure universal access to iodized salt and raise awareness in the community about the importance of using iodized salt.